Proving the Effectiveness of the Fundamentals of Robotic Surgery (FRS) Skills Curriculum: A Single-blinded, Multispecialty, Multi-institutional Randomized Control Trial. Issue 2 (August 2020) - Satava, Richard M.; Stefanidis, Dimitrios; Levy, Jeffrey S.; Smith, Roger; Martin, John R.; Monfared, Sara; Timsina, Lava R.; Darzi, Ara Wardkes; Moglia, Andrea; Brand, Timothy C.; Dorin, Ryan P.; Dumon, Kristoffel R.; et al.
Abstract : Objective: To demonstrate the noninferiority of the fundamentals of robotic surgery (FRS) skills curriculum over current training paradigms and identify an ideal training platform. Summary Background Data: There is currently no validated, uniformly accepted curriculum for training in robotic surgery skills. Methods: Single-blinded parallel-group randomized trial at 12 international American College of Surgeons (ACS) Accredited Education Institutes (AEI). Thirty-three robotic surgery experts and 123 inexperienced surgical trainees were enrolled between April 2015 and November 2016. Benchmarks (proficiency levels) on the 7 FRS Dome tasks were established based on expert performance. Participants were then randomly assigned to 4 training groups: Dome (n = 29), dV-Trainer (n = 30), and DVSS (n = 32) that trained to benchmarks and control (n = 32) that trained using locally available robotic skills curricula. The primary outcome was participant performance after training based on task errors and duration on 5 basic robotic tasks (knot tying, continuous suturing, cutting, dissection, and vessel coagulation) using an avian tissue model (transfer-test). Secondary outcomes included cognitive test scores, GEARS ratings, and robot familiarity checklist scores. Results: All groups demonstrated significant performance improvement after skills training ( P < 0.01). Participating residents and fellows performed tasks faster (DOME and DVSS groups) and with fewer errors than controls (DOME group; P < 0.01). Inter-rater reliability was high for the checklist scores (0.82–0.97) but moderate for GEARS ratings (0.40–0.67). Conclusions: We provide evidence of effectiveness for the FRS curriculum by demonstrating better performance of those trained following FRS compared with controls on a transfer test. We therefore argue for its implementation across training programs before surgeons apply these skills clinically. Abstract : Supplemental Digital Content is available in the text